Measurement of tensor polarization observables in deuteron photodisintegration; Advanced Research Workshop on High Energy Spin Physics (NATO ARW DUBNA-SPIN-03) (10; 2003; Dubna) - Nikolenko D. M.; Arenhovel H.; Barkov L. M.; Stibunov V. N. Victor Nikolaevich (2004, 2004)
В фонде НТБ ТПУ отсутствует